Enterprise Mac security : MAC OS X Snow Leopard - Edge, Charles S.; Barker, William (New York : Apress, 2010)
Contains detailed Mac OS X security information, and walkthroughs on securing systems, including the new Snow Leopard operating system. You'll learn the newest security techniques on Mac OS X, details of the new Mac OS X Snow Leopard Operating System for the desktop and server, and how to secure these systems, Mac forensics and Mac hacking, Apple wireless security, and more.
PART I: The big picture. Security quick-start ; Services, daemons, and processes ; Securing user accounts ; File system permissions ; Review logs and monitoring -- PART II: Securing the ecosystem. Application signing and sandbox ; Securing web browsers and e-mail ; Malware security: combating viruses, worms, and root kits ; Encrypting files and volumes -- PART III: Network traffic. Securing network traffic ; Setting up the Mac OS X firewall ; Securing a wireless network -- PART IV: Sharing. File services ; Web site security ; Remote connectivity ; Server security -- PART V: Securing the workplace. Newtork scanning, intrusion detection, and intrusion prevention tools ; Backup and fault tolerance ; Forensics -- Appendix A: Xsan security -- Appendix B: InfoSec acceptable use policy -- Appendix C: CDSA -- Appendix D: Introduction to cryptography.
Includes index.
User level: Beginning -Intermediate.
Keywords: Mac OS; Computer security